PENERAPAN GAME EDUKASI BERBASIS ANDROID DAN GAMBAR BAGI SISWA SEKOLAH DASAR - Chrisnaji Banindra Yudha (Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The objective of this study is to discover the effectiveness of: (1) Android-based mathematics instructional media in learning multiplication, (2) image-based mathematics instructional media in learning multiplication and (3) learning multiplication without any media. This study is an experimental one that uses Randomized Pretest-Posttest Control Group design. In the experiment, observations on three learning groups were conducted. The first experimental group was given a treatment in the form of Android-based mathematics instructional media, the second experimental group received an image-based mathematics instructional media, and the control group did not use any media. The research population was all 2th-grade students in South Tangerang Rempoa 4 Elementary School and with the sample of IIA, IIB, and IIC class students. The research instrument was a test of fractions that had been tested with Alpha 0.826. The data analysis technique used was Anova and then followed by Scheffe test. The results of the study show that: (1) there is a significant effectiveness difference between mathematics learning that is Android-based, image-based, and the one that uses no media in learning fractions among the 5th-grade students of South Tangerang Rempoa 4 Elementary School, (Fh = 6,121 > Ft (0,05) = 3,10); (2) there is a significant difference between the effectiveness of Android-based and image-based mathematics instructional media in learning multiplication, (sig. (p) = 0,023 < 0,05); (3) there is a significant difference between the effectiveness of learning multiplication by using Android-based mathematics instructional media and not using any media (sig. (p) = 0,005 < 0,05); and (4) there is no significant difference between the effectiveness of learning multiplication by using image-based media and not using any media, (sig. (p) = 0,811 > 0,05). These show that Android-based mathematics instructional media is better than the image-based one, learning with image-based media is not any better than learning without media, and the Android-based mathematics instructional media is the most effective tool compared to that of image-based media and using no media. Abstrak Tujuan penelitian ini adalah mengetahui keefektifan: (1) game edukasi berbasis android, (2) media gambar, dan (3) tanpa media dalam pembelajaran matematika materi perkalian. Jenis penelitian adalah eksperimental dengan desain Randomized Pretest-Posttest Control Group Design. Dalam proses eksperimen dilakukan pengamatan pada tiga kelompok pembelajaran yaitu kelompok eksperimen satu yang diberi treatment dengan game edukasi berbasis Android, kelompok eksperimen dua dengan media gambar, dan kelompok kontrol dengan tanpa media. Populasi penelitian adalah semua peserta didik kelas II SDN Rempoa 4 Tangerang Selatan dengan sampel peserta didik kelas II A, II B, dan II C. Instrumen penelitian adalah tes soal perkalian yang telah di uji coba dengan Alpha 0,826. Teknik analisis data menggunakan Anava yang dilanjutkan dengan uji Scheffe. Hasil penelitian menunjukkan bahwa: (1) ada perbedaan yang signifikan keefektifan di antara pembelajaran matematika menggunakan game edukasi berbasis Android, media gambar, dan tanpa media dalam Pembelajaran perkalian kelas II SDN Rempoa 4 Tangerang Selatan, (Fh = 6,121 > Ft (0,05) = 3,10); (2) ada perbedaan yang signifikan keefektifan game edukasi berbasis Android dan media gambar dalam pembelajaran perkalian, (sig. (p) = 0,023 < 0,05); (3) ada perbedaan yang signifikan keefektifan game edukasi berbasis Android dan tanpa media dalam pembelajaran perkalian, (sig. (p) = 0,005 < 0,05); dan (4) tidak ada perbedaan yang signifikan keefektifan media gambar dan tanpa media dalam pembelajaran perkalian, (sig. (p) = 0,811 > 0,05). Hal ini menunjukkan bahwa game edukasi berbasis Android lebih baik dari pada media gambar, media gambar tidak lebih baik dari pada tanpa media, dan game edukasi berbasis Android paling efektif diantara media gambar dan tanpa media. Kata Kunci: game edukasi, android, matematika, dan sekolah dasar